Characterization of immobilized biomass by amplified rDNA restriction analysis (ARDRA) in an anaerobic sequencing-batch biofilm reactor (ASBBR) for the treatment of industrial wastewater - Sarti, Arnaldo [UNESP]; Pozzi, Eloisa; Zaiat, Marcelo (Instituto de Tecnologia do Paraná - Tecpar, 2012)
The performance of an anaerobic sequencing-batch biofilm reactor (ASBBR- laboratory scale- 14L )containing biomass immobilized on coal was evaluated for the removal of elevated concentrations of sulfate (between 200 and 3,000 mg SO4-2·L-1) from industrial wastewater effluents. The ASBBR was shown to be efficient for removal of organic material (between 90% and 45%) and sulfate (between 95% and 85%). The microbiota adhering to the support medium was analyzed by amplified ribosomal DNA restriction analysis (ARDRA). The ARDRA profiles for the Bacteria and Archaea domains proved to be sensitive for the determination of microbial diversity and were consistent with the physical-chemical monitoring analysis of the reactor. At 3,000 mg SO4-2·L-1, there was a reduction in the microbial diversity of both domains and also in the removal efficiencies of organic material and sulfate.
Keywords: sulfate removal; support medium; endonucleases; ARDRA; batch reactor; ASBBR